176k views
1 vote
Is -2/3(-12b-6+9b-18) equivalent to 2(b+8)? Show your work.
please help.

User Idoby
by
5.1k points

2 Answers

3 votes

Is -2/3(-12b-6+9b-18) equivalent to 2(b+8)?

To find out, simplify the left side.

Multiply every term in the parentheses by 2/3.

(8b + 4 - 6b + 12)

Simplify.

(2b + 16)

Factor out 2.

2(b + 8)

We conclude that -2/3(-12b-6+9b-18)

equals 2(b + 8).

User Laurence Gonsalves
by
4.4k points
6 votes

Answer:

Explanation:

-2/3(-3b-24) = 2(b+8)

6b/3+48/3 = 2b+16

2b+16 = 2b+16 => equivalent

User Eesiraed
by
4.2k points